2008
DOI: 10.1159/000155222
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Left Lateral Liver Sectionectomy: A Safe, Efficient, Reproducible Technique

Abstract: Background: Laparoscopic left lateral sectionectomy (LLLS) is procedure with potential for future transformation into a primarily laparoscopic procedure where surgeons can safely develop laparoscopic experience and gain proficiency. Methods: Between August 2004 and December 2007, 80 patients underwent laparoscopic liver resections in our unit, 30 of these were left lateral sectionectomies. The indications for surgery were both oncological and non-oncological. Results: 30 LLLS were performed. Median operative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 27 publications
1
47
0
1
Order By: Relevance
“…Virtually all left sections (removal of segments 2 and 3) are performed laparoscopically (Abu Hilal and Pearce, 2008). These results are consistent with experience in other centres (Nguyen et al, 2009).…”
Section: Minimally Invasive Surgerysupporting
confidence: 86%
“…Virtually all left sections (removal of segments 2 and 3) are performed laparoscopically (Abu Hilal and Pearce, 2008). These results are consistent with experience in other centres (Nguyen et al, 2009).…”
Section: Minimally Invasive Surgerysupporting
confidence: 86%
“…From a previous series of 174 patients undergoing LLR, it has been demonstrated that increasing experience is associated with a reduction in operating time, conversion rate, blood loss and operative morbidity whilst at the same time performing more complex resections and more resections for malignant disease. Some authors suggest that a learning curve of approximately 60 cases is required to become fully familiar with the techniques of LLR [30] as suggested by others [26,31]. However, more latterly some of the cases reported in the current series have been done by senior HPB surgical trainees under consultant supervision making the learning curve within this series more difficult to evaluate.…”
Section: Discussionmentioning
confidence: 92%
“…No hand-assisted or ‘hybrid’ techniques [26] were used. Our group have previously described the technique for left lateral sectionectomy, major hemi-hepatectomy and segmentectomies [8,11,24]. …”
Section: Methodsmentioning
confidence: 99%
“…In expert hands, the feasibility, safety and efficiency of the laparoscopic approach have been demonstrated when appropriate criteria are applied to patient selection [2,3,4,5,6,7,8,9,10,11]. In a recent review including approximately 2,800 patients, the mortality and morbidity rates were reported to be 0.3 and 10.5%, respectively [1].…”
Section: Introductionmentioning
confidence: 99%